Synthesis of Ti2SnC under Optimized Experimental Parameters of Pressureless Spark Plasma Sintering Assisted by Al Addition - Chen Lu; Yue Wang; Xiaofan Wang; Jianfeng Zhang (Advances in Materials Science and Engineering)
As an effective and novel rapid sintering technology with the advantages of fast heating speed and short sintering time, SPS has been applied to the research and development of various materials. After sintering at 1325°C, Ti5Sn3 and Sn occurred as impurities accompanying the synthesis of Ti2SnC with a raw powder mixture of Ti/Sn/C = 2/1/1 (molar ratio). But by addition of 0.2 molar Al, and further optimization of sintering parameters at 1400°C for 10 min, almost fully pure Ti2SnC was obtained with a clear layered microstructure. The reaction mechanism analysis suggests that this beneficial effect of Al could be attributed to the suppression of decomposition of Ti2SnC by formation of Ti2SnxAl1−xC solid solution at a high sintering temperature. The present study reports a novel route to synthesize Ti2SnC by PL-SPS with a self-designed graphite die, and Al was also proposed as a sintering aid to remove impurities.